Atmospheric Wet Deposition of PCDD/Fs in the Ambient Air - Xueying Tian; Kangping Cui; Hwey-Lin Sheu; Yen-Kung Hsieh; Fanxuan Yu (Aerosol and Air Quality Research)
Abstract Wet deposition is an important mechanism for removing air pollutants from the atmosphere. The total PCDD/Fs-WHO2005-TEQ wet deposition from 2018–2020 was investigated for Beijing and Tianjin City in this study. In addition, the gas-particle partitioning of wet deposition, the total PCDD/Fs-WHO2005-TEQ concentrations in the rain, the PM2.5-bound total PCDD/Fs-WHO2005-TEQ content, and the PM2.5 concentration were also studied for Beijing and Tianjin City, respectively. Between 2018 to 2020, as a whole, the average seasonal variations in PCDD/F wet deposition fluxes in spring, summer, fall, and winter were 50.50, 41.47, 23.03 and 16.76 pg WHO2005-TEQ m–2 month–1, respectively, while in Tianjin, they were 35.30, 42.40, 13.37, and 14.77 pg WHO2005-TEQ m–2 month–1, respectively. Because the two cities have more rainfall in spring and summer than they do in fall and winter, rainfall has a significant influence on the wet deposition flux. In regard to PCDD/Fs-WHO2005-TEQ in the rain, in Beijing, the average total PCDD/Fs-WHO2005-TEQ concentration in the rain in spring, summer, fall, and winter were 1.70, 0.39, 1.42, and 1.52 pg WHO2005-TEQ L–1, respectively, while those in Tianjin, were 1.73, 0.42, 1.35, and 1.88 pg WHO2005-TEQ L–1, respectively. The above results show that the total PCDD/Fs-WHO2005-TEQ concentrations in the rain are significantly lower in summer, which is mainly due to the fact that in summer, the total PCDD/Fs-WHO2005-TEQ concentrations in the air are lower, and the proportion of the gas phase is increased. When the total PCDD/Fs-WHO2005-TEQ concentrations in the air are washed away by a heavy rainfall, the PCDD/F concentrations are diluted.